Analisis studi kelayakan bisnis UMKM Dewi-Dewi Handycraft ditinjau dari aspek manajemen dan sumber daya manusia - Prayogi, Adha Herfian; Panatagama, Ahmad Ramapanji; Solekah, Nihayatu Aslamatis (Maliki Interdisciplinary Journal, 2024)
This research aims to determine the business feasibility study in terms of the human resources aspect of Dewi-dewi UKM in Malang, East Java. This research uses a descriptive qualitative method that describes objects using primary data collection techniques. The analytical tool in this research uses a Likert scale which adds up the scores from all question items. The results of the research show that this UKM has good criteria in the Likert scale assessment so that this UKM is suitable to be run.